Meta-Analysis of Long-Term Efficacy of Proliferative Diabetic Retinopathy Based on Intelligent Medical Treatment. (23rd September 2022) - Fang, Fang; Cao, Yanjie; Chen, Keyan; Su, Xingjie; Qi, Yanxiu; Zhang, Di; Liu, Hongwei
Abstract : In order to solve some problems of subhealth and high chronic diseases, the diagnosis and treatment of value-added diabetic retinopathy are studied. In particular, diabetes, a high chronic disease, poses a great threat to people's health. With the continuous improvement of national health awareness, the medical field also begins to pay more attention to the diagnosis and treatment of value-added diabetic retinopathy. In order to improve the long-term treatment of value-added diabetic retinopathy through intelligent medical monitoring and systematic scientific efficacy analysis and evaluation, the purpose of this study is to explore how to effectively achieve the meta-analysis of long-term efficacy of proliferative diabetic retinopathy through intelligent medical treatment. Through the study of diabetic retinopathy, the system can help doctors to achieve unlimited further signs of parameter acquisition and transmission and build more mature after treatment of the results of the monitoring platform. At the same time, a conclusion based on vitrectomy was proposed to effectively improve the surgical efficacy of patients with proliferative diabetic retinopathy.